Food, farms & solidarity : French farmers challenge industrial agriculture and genetically modified crops - Heller, Chaia (New ecologies for the twenty-first century., 2013)
Chaia Heller follows one of France's largest farmers' unions as it joins with peasants internationally to contest the hegemony of genetically modified foods, free trade, and industrial agriculture.